Finding your roots with Henry Louis Gates, Jr. Season 5 [videorecording (DVD)] - Streeter, Sabin; Gurland-Pooler, Hazel (PBS, 2019)
Dr. Gates uses genealogy and DNA science to trace the ancestry of celebrities.